Catalytic Syntheses of Pyrano[3,2-c]Quinolone and -Quinoline Derivatives and their Potential Therapeutic Agents - Aly, Ashraf A.; Abd El-Naby, Hisham A.; Ahmed, Essam Kh.; Gedamy, Sageda A.; Alshammari, Mohammed B.; Ahmad, Akil; Bräse, Stefan (Current Organic Chemistry, 2025)
Pyrano[3,2-c]quinolone and pyrano[2,3-c]quinoline, as promising molecules, have garnered more attention due to their interesting biological properties. This review dealt with the catalytic synthesis of the former candidates in the last 20 years. Multi-component reactions (MCRs) are synthetic routes that produce a single product from three or more reactants in a one-pot step procedure. We herein reported on the advantages of catalysis in synthesizing the target compounds using the MCR sequence. We also discussed the mechanism and explained the chosen catalyst's utility in the target molecules' selectivity. Finally, this recent review focuses on the biological applications of these molecules as anticancer, antimicrobial activities, anti-diabetic, anti-inflammatory, anti-Alzheimer, and antitubercular agents.
Keywords: anti-Alzheimer